Hot corrosion behavior of ZrB2-HfB2 solid solutions in KCl and K2SO4 at 1500 °C. Issue 18 (15th December 2017) - Sitler, Steven J.; Raja, Krishnan S.; Charit, Indrajit
Abstract: Novel electrode coating materials are needed for coal-fired magnetohydrodynamic (MHD) direct-current extraction power plants. Addition of potassium salt to increase the conductivity of coal plasma combined with high temperature render the service conditions extremely arduous. Therefore, the electrode coating materials must possess certain properties including high-temperature corrosion resistance, high-temperature oxidation resistance, and adequate electrical conductivity. In this work, those very properties of three different compositions of transition metal diboride solid solutions of HfB2 -ZrB2 are studied. Two main approaches of oxidation mitigation methods were employed: adding chemical dopants, such as Hf and La, and performing pre-anodization on the samples to create a protective oxide coating. Thermogravimetric experiments were run at different partial pressures of oxygen to determine the high-temperature oxidation resistance of these boride ceramics. In addition, two different salt coatings (KCl and K2 SO4 ) were applied to the surface of the samples to test their hot corrosion resistance. High-temperature polarization resistance tests were also conducted to measure the electrical resistivity. The addition of lanthanum aided in long term oxidation and corrosion protection, with a parabolic rate constant, Kp = 1.33 × 10 −5  kg 2 /m 4  s, a 40% improvement over the sample without the addition of lanthanum under the same conditions. Anodization, however, proved disadvantageous when combined with either lanthanum or a corrosive environment.